Gambaran Visum et Repertum kasus kekerasan seksual khususnya perkosaan di RS Bhayangkara Manado periode Juli 2015–Juni 2016 - Pagayang, Koresy Trisna; Mallo, Johannis; Tomuka, Djemi (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Visum Et Repertum is an description made by a doctor at the request of official investigator about the results of medical examination on human, whether alive or dead, or which suspected as part of.human’s body. Based on medical sciences and under the oath for the sake of judiciary. The increasing of rape cases are related to the socio-cultural aspect. The culture is increasingly open, he way woman’s dress also more tempting than before, and sometimes with variety of expensive jewelry, the habit to traveling alone are dominant fctor that affect the high frequency of rape cases. The purpose of this research is to find out the results of visum et repertum on rape victims period july 2015 – juny 2016 at bhayangkaramanado hospital. The result of this study from 110 case is 17 people was pregnant and 62 people was not pregnant, and 31 people which is not clear in this case did not do investigations. Obtained from distribution by age mostly from age 14 are 17 people, obtained from distribution based on resort is Polresta Manado, this study proves that the results of visum et repertum can be found in existence of sexual violence to victimsKeywords: Visum Et Repertum, rape victims